Design of Portable Cool Box Stand Frame to Facilitate Refueling - Enty Nur Hayati; Firman Ardiansyah Ekoanindiyo; Antoni Yohanes (Jurnal Serambi Engineering, 2024)
The SN Multi-Business Cooperative (KSU) is located in Getasan District, Semarang Regency. This cooperative collect cow's milk which is cooled to a certain temperature and sent to milk factories and restaurants and cafes. The problem that often arises is that milk that has been sent to the milk factory can be rejected for various reasons. To carry processed milk, every motorbike rider uses a basket bag made of thick cloth which is mounted on the back of the motorbike. Using this basket bag is less practical because if the driver wants to refuel, the basket bag must be removed first. The design of the portable cool box mounting frame makes it easier for drivers to refuel. The portable cool box's mounting frame is designed to transport milk more effectively, using a cooling stand that can be removed, which is more ergonomic, making it easier to refuel.